TINGKAT KENYAMANAN AREA BERVEGETASI DI TAMAN MERDEKA, KOTA METRO - Muhammad Hanif Alfatah; Gunardi Djoko Winarno; Agus Setiawan; Irwan Sukri Banuwa (Jurnal Belantara, 2022)
Green open space has an ecological function because it contains constituent trees that can provide comfort in the form of coolness to the surrounding area. This study aims to determine the level of comfort based on the Comfort Index/Temperature Humidity Index (THI) by measuring the temperature and humidity at Taman Merdeka green open space, Metro City, Lampung Province. The method used in this research is direct observation method, with sampling using saturated sampling method. The data that has been obtained is tabulated and analyzed using the convenience / THI method. The results showed that there were 129 individuals of the Taman Merdeka green open space composed of 14 species, with a tree density value of 81,13 trees / ha, a total canopy area of 8.545,29 m2. The comfort level at Taman Merdeka RTH is included in the Medium category with an average THI value at the three data collection locations of 25,99. The condition of the open green open spaces of Taman Merdeka, in the form of the number of individual trees, tree types, tree density, and tree canopy cover area can affect the temperature and humidity in the green open space so that the level of comfort will also be affected. The condition of the Taman Merdeka green open space is included in the Medium category, the hope is that the manager of the Taman Merdeka green open space can improve it so that visitors feel comfortable when doing activities in this green open space.